How can i prove this union?

sinA * sinB = 1/2 * [cos(A – B) – cos(A + B)]

RS = 1/2 * [cosA cosB + sinA sinB – (cosA cosB – sinA sinB)]

= 1/2 * (cosA cosB + sinA sinB – cosA cosB + sinA sinB)

= 1/2 * (2 * sinA sinB)

= sinA sinB = LS

1/2[cos(A-B)-cos(A+B)]

=1/2[(cosAcosB+sinAsinB)-(cosAcosB-sinAsinB)]

=1/2[2sinAsinB]

=sinAsinB

cos(A-B)=cos(A)*cos(B)+sin(A)*sin(B)

cos(A+B)=cos(A)*cos(B)-sin(A)*sin(B)

cos(A-B)-cos(A+B)= cos(A)*cos(B)+sin(A)*sin(B)-

(cos(A)*cos(B)-sin(A)*sin(B))=

2*sin(A)*sin(B)

So sin(A)*sin(B)=0.5(cos(A-B)-cos(A+B))

Latest posts by Answer Prime (see all)

- 21 june, gemini or cancer?!? - January 25, 2023
- What idea is the narrator in ‘exhalation’ most clearly promoting to the reader? - January 25, 2023
- How many neutrons does the isotope N-14 have? - January 25, 2023